Blue Dolphin Expedition to Labrador - Nutt, David C. (ARCTIC, 1949)
Commander David C. Nutt, U.S.N.R., of Dartmouth College, Hanover, New Hampshire, is to lead a scientific expedition to Labrador in June 1949. The following is a description of his vessel, which will sail under the auspices of the Arctic Institute of North America. The Blue Dolphin, designed by W. J. Roue and built by the Shelburne Shipbuilders, Ltd., Nova Scotia in 1926, has lines similar to the famous Bluenose. Heavily lumbered with 9-inch double frames and heavy planks, she has an overall length of 100 feet, a beam of 22 feet, and a draught of 12 feet. Her registered net tonnage is 68, and her gross tonnage 91. It is planned to sheathe the hull with greenheart, a South American hardwood which polishes instead of splintering under ice abrasion. The stem will be strengthened and a heavy iron shoe added. For power, a new 140 hp. Wolverine 4-cylinder, 4-cycle, 83-inch by 104-inch heavy duty diesel engine was installed in 1947. This engine provides a nice compromise between fuel economy and speed, and gives a cruising speed of 7 knots with a maximum of 8 knots. Additional fuel tanks have been added to give the Blue Dolphin a cruising range of over 4000 miles. The present two-masted schooner rig with Marconi main has a sail area of over 4000 feet, but will be reduced about 20% by cutting the bowsprit down to a 4-foot stub and shortening the main boom approximately 7 feet. This will leave an adequate sail area, and maneuvre the vessel under sail alone in the event of damage to the screw, but will eliminate the long projecting bowsprit and main boom, which are undesirable in northern operation. . Sails are considered a desirable auxiliary which can provide for fuel economy by helping the vessel along in a fair wind and which may save the vessel in the event of damage to rudder or screw, a real possibility in northern navigation. The Blue Dolphin will carry an 18-foot power launch and two or three fisherman dories for boats. It is also planned to add hydrographic and trawl winches, and deep-sea sounding gear, samplers, ...